Improving STING Agonist Delivery for Cancer Immunotherapy Using Biodegradable Mesoporous Silica Nanoparticles. Issue 10 (21st July 2020) - Park, Kyung Soo; Xu, Cheng; Sun, Xiaoqi; Louttit, Cameron; Moon, James J.
Abstract: Stimulator of interferon genes (STING) activation by intratumoral STING agonist treatment has been recently shown to eradicate tumors in preclinical models of cancer immunotherapy, generating intense research interest and leading to multiple clinical trials. However, there are many challenges associated with STING agonist‐based cancer immunotherapy, including low cellular uptake of STING agonists. Here, biodegradable mesoporous silica nanoparticles (bMSN) with an average size of 80 nm are developed for efficient cellular delivery of STING agonists. STING agonists delivered via bMSN potently activate innate and adaptive immune cells, leading to strong antitumor efficacy and prolonged animal survival in murine models of melanoma. Delivery of immunotherapeutic agents via biodegradable bMSN is a promising approach for improving cancer immunotherapy. Abstract : Biodegradable mesoporous silica nanoparticles enhance cellular delivery of stimulator of interferon genes (STING) agonists and achieve greater antitumor therapeutic efficacy than free STING agonists in murine models of melanoma. Biodegradable mesoporous silica nanoparticles are a promising platform for cancer immunotherapy.